MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS PESERTA DIDIK DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATA PELAJARAN MATEMATIKA DI SMK NEGERI 3 MEDAN - Azhari, Vira; Khayroiyah, Siti; Ilham, Mira (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2024)
his study aims to improve student learning outcomes and engagement through the implementation of the Problem-Based Learning (PBL) model supported by interactive teaching media at SMK Negeri 3 Medan. Conducted using a classroom action research (CAR) approach, the study involved three cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 36 students from class X FKK 2. Interactive media such as Canva and Kahoot were utilized to enhance student involvement in the learning process.The results of the study indicate that the application of PBL with interactive media significantly improved student learning outcomes, with the average score rising from 78.14 in the pre-cycle to 93.71 in the third cycle. Additionally, student absorption rates increased from 81.57% in Cycle I to 93.71% in Cycle III, reflecting an "excellent" category. The classical completeness reached 100% in Cycle III, indicating that all students achieved the learning objectives. Student activity also showed improvement, with the average activity level in Cycle III reaching the "excellent" category.Overall, the implementation of the PBL model supported by interactive teaching media proved effective in enhancing student learning outcomes and engagement. This model not only improved material comprehension but also enhanced student involvement in the learning process. The study provides significant contributions to teaching practices by demonstrating that interactive technology can enrich learning experiences and improve academic success.